A comparison of the air pollution of gasoline and CNG driven car for Malaysia - Jahirul, M.I.; Saidur, Rahman; Hasanuzzaman, M.; Masjuki, Haji Hassan; Kalam, M.A. (International Journal of Mechanical and Materials Engineering, 2007)
In order for saving the constrained resources and preservation of environment, the natural gas is a proven low cost and low emission alternative fuel to petroleum fuels for all types of motor vehicles. It is being widely used throughout the globe. In Malaysia, still millions of vehicles are plying on use of petroleum fuels. These fuels release huge emissions to the environment. Definitely, this adversely affects the natural ecosystem. In this backdrop, a study is felt important to predict the trend of emissions of anti-body gases released by cars in Malaysia for use of liquid fuels and natural gas between 2006 and 2020. The growth of vehicles demand has been considered alongside. The study reveals that current emission levels of different anti-body gases are huge and these can be significantly reduced by converting liquid fuel based engine into the natural gas based engine.